Um "cemitério ubíquo": história e literatura no Brasil dos anos 1970 (ArtCultura, 2010)
abstractA imagem da história como "cemitério ubíquo" encontra-se no livro de poemas de Afonso Henriques Neto e Eudoro Augusto, O misterioso ladrão de Tenerife, publicado em 1972 e tido como uma das obras características da contracultura brasileira, ou da "poesia do sufoco" produzida pela geração do "desbunde", como então se dizia. Tomando o poema como fonte histórica (Adorno, Benjamin) e observando o seu teor testemunhal (Seligmann), este trabalho busca analisar indícios de como a história foi concebida e sentida no Brasil sob a ditadura civil-militar, bem como a inflexão sofrida na relação sujeito-história, levando em consideração as questões éticas postas à análise crítica da experiência social traumática.PALAVRAS-CHAVE: ditadura civil-militar; poesia contracultural; experiência histórica traumática.ABSTRACT: The image of History as an "ubiquitous graveyard" is found in the book of poems called The mysterious thief of Tenerif, by Afonso Henriques Neto and Eudoro Augusto, published in the year of 1972. It is a very characteristic work of the Brazilian contra-culture, specially of the "breathless poetry" made by that "alienated" generation, as it was then usually said. Considering a poem as a historical source (Adorno, Benjamin), and the "testimonial contents" of this poetry (Seligmann), the present article searches to analyze the changes in the relation between individuals and History, taking in account some ethical questions that the traumatic social experience puts to a critical thinking.KEYWORDS:civil-military dictatorship; contra-cultural poetry; traumatic historical experience.